The Influence of Teacher Leadership Style on Student Discipline at SMA Negeri 1 Ulubongka - Lapa, Selfi; Andi Indriani Ibrahim; Wisra Matalatta; Lindanur Sipatu; Rosida P. Adam (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of teacher leadership style on student discipline at SMA Negeri 1 Ulubongka using a quantitative causal-descriptive approach. The results indicate that teacher leadership style has a positive and significant effect on student discipline (p = 0.009 < 0.05). The regression coefficient of 0.437 shows that improved teacher leadership increases student discipline, while the coefficient of determination (R² = 0.528) indicates that leadership explains 52.8% of its variation. Effective leadership through motivation, communication, decision-making, and learning management is therefore essential for strengthening student discipline. Keywords: Teacher Leadership Style; Student Discipline; Human Resource Management; Organizational Behavior